A Checklist of Fissidens species (Musci: Fissidentaceae) of Nepal - Pradhan, N.; Joshi, S. D. (Our Nature, 2007)
This paper includes 42 species and 7 varieties of Fissidens recorded from Nepal. The distribution of this genus in various geographical areas within the altitudinal range of 100 m to 3400 m has been mentioned. Fissidens sylvaticus var. calcuttense Gangulee, Fissidens sylvaticus var. auriculatus (C. Muell.) Gangulee and Fissidens strictus Hook. & Wilson have been recorded for the first time in Nepal. Keywords: Fissidens, Bryophytes, Mosses, Conservation doi:10.3126/on.v4i1.504 Our Nature Vol. 4(1) 2006 pp61-68